Recent advances in polyphenols nanocarriers against breast cancer therapy focus on in vitro studies: literature review - Ribeiro, Mariana Fernandes; Cadoná, Francine Carla; Gomes, Patricia (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
Cancer is considered a severe public health problem worldwide. Among the most incident cases, breast cancer, which affects many women in the entire world, can be mentioned. Currently, there are well-established protocols for the treatment of this type of cancer. However, cancer treatment presents collateral effects that can compromise the patient’s quality of life. Therefore, studies have suggested that plants and fruits rich in polyphenols have antitumor activity, decrease chemotherapy resistance, and reduce side effects caused by chemotherapy. However, most of these compounds have low bioavailability making their potential pharmacological challenging. Therefore, the search for carriers that can efficiently protect and transport these bioatives to tumor cells is of great interest. In this sense, nanostructured systems can be included as the delivery of bioactive molecules and drugs. Thus, this study aimed to report the current studies using nanocarriers containing phenolic compounds to evaluate their antitumor effect against breast cancer cells. Data collection included the virtual databases Science Direct and Web of Science using the descriptors: nanoparticles and polyphenols and breast cancer, for experimental articles published from 2015 to September 15, 2020. The search resulted in a total of 1346 articles, of 37 met the inclusion criteria. The studies have demonstrated the efficiency of nanostructures containing polyphenols against cancer cells, suggesting excellent perspectives in the use of nanotechnology combined with bioactive compounds in the treatment of breast cancer.